Total weight loss induces the alteration in thyroid function after bariatric surgery - Tian, Ziru; Nie, Yuntao; Li, Zhengqi; Wang, Pengpeng; Zhang, Nianrong; Hei, Xiaofan; Ping, An; Liu, Baoyin; Meng, Hua (Frontiers in Endocrinology, 2024)
Background Bariatric surgery is an effective approach to weight loss, which may also affect thyroid function. However, alteration in thyroid-stimulating hormone (ΔTSH) and thyroid hormones after bariatric surgery and the relationship between thyroid function and postoperative weight loss still remains controversial. Methods Data were collected from euthyroid patients with obesity who underwent sleeve gastrectomy and Roux-en-Y gastric bypass from 2017 to 2022. The alterations of free thyroxine (FT4), free triiodothyronine (FT3), total thyroxine (TT4), total triiodothyronine (TT3), and TSH were calculated 1 year after surgery. Pearson correlation analysis was used to assess the correlation between the percentage of total weight loss (%TWL) and ΔTSH. Multivariable linear regression was utilized to determine the association between %TWL and ΔTSH. Results A total of 256 patients were included in our study. The mean %TWL was 28.29% after 1 year. TSH decreased from 2.33 (1.67, 3.04) uIU/mL to 1.82 (1.21, 2.50) uIU/mL (P < 0.001), FT3 decreased from 3.23 ± 0.42 pg/mL to 2.89 ± 0.41 pg/mL (P < 0.001), FT4 decreased from 1.11 ± 0.25 ng/dL to 1.02 ± 0.25 ng/dL (P < 0.001), TT3 decreased from 1.13 (1.00, 1.25) ng/mL to 0.89 (0.78, 1.00) ng/mL (P < 0.001), and TT4 decreased from 8.28 ± 1.69 ug/mL to 7.82 ± 1.68 ug/mL 1 year postoperatively (P < 0.001). %TWL was found to be significantly correlated to ΔTSH by Pearson correlation analysis (Pearson correlation coefficient = 0.184, P = 0.003), indicating that the more weight loss, the more TSH declined. After adjusting for covariates in multivariable linear regression, %TWL was found to be independently associated with ΔTSH (β = 0.180 [95% confidence interval (CI), 0.048 – 0.312], P = 0.008). Moreover, %TWL was divided into 3 categorical groups (%TWL ≤ 25%, 25% < %TWL ≤ 35%, and %TWL > 35%) for further exploration, and was also found to be an independent predictor for ΔTSH after adjusting for covariates in multivariable linear regression (β = 0.153 [95% CI, 0.019 – 0.287], P = 0.025). Conclusion TSH, FT4, FT3, TT4, and TT3 decrease significantly 1 year after bariatric surgery. The decline in TSH is independently mediated by postoperative weight loss; the more the weight loss, the more the TSH decrease.